2018
DOI: 10.1111/head.13442
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Persistent Headache at 18 Months Following Accidental Dural Puncture in the Obstetric Population: A Prospective Service Evaluation in 45 Patients

Abstract: Objective The aim of the prospective longitudinal service evaluation was to reveal the incidence of persistent headache at 18 months following accidental dural puncture with a 16‐gauge Tuohy needle. This followed an observation that a subset of female patients was presenting to the local pain medicine clinic with persistent headache following an accidental dural puncture. Background Two thirds of patients with an accidental dural puncture develop post dural puncture headache that is believed to be a self‐limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…They noted similar prevalence rates of headache in postpartum women to that found in previous studies. In their study, 30% of 39 patients who suffered UDP reported persistent headache symptoms at 18 months postpartum 5 . Half reported new headaches, and half reported worsening of preexisting headache.…”
Section: Duration Of Pdphmentioning
confidence: 91%
See 1 more Smart Citation
“…They noted similar prevalence rates of headache in postpartum women to that found in previous studies. In their study, 30% of 39 patients who suffered UDP reported persistent headache symptoms at 18 months postpartum 5 . Half reported new headaches, and half reported worsening of preexisting headache.…”
Section: Duration Of Pdphmentioning
confidence: 91%
“…The most frequent occurs following an unintended dural puncture (UDP) with the large bore Tuohy‐type needle commonly used for the placement of epidural catheters to manage labor pain in the parturient. UDP occurs in 0.7%–1.5% of parturients, and mounting data suggest UDP precipitates new or worsened headache after childbirth in up to a third of women who experience this complication 1–5 . In this paper, we will seek to bridge the literature between two specialties by comparing both the definition of PDPH and its known risk factors from both the neurology and OB anesthesia perspective.…”
Section: Introductionmentioning
confidence: 99%
“…These findings point to a fact that PDPH is not solely self-limiting condition and necessitate follow-up even for cases with mild manifestations. In line with this assumption, Gauthama et al [34] reported that at 18 months after the procedure, PDPH persisted in 30%, worsened in 15% of patients and another 15% of patients developed new onset headache, so concluded that PDPH can no longer be considered a self-limiting condition.…”
Section: Discussionmentioning
confidence: 91%
“…Twenty‐five participants had a contrast‐enhanced MRI of the head; none showed any features consistent with intracranial hypotension. We suggest that short‐term cerebrospinal fluid loss and concomitant intracranial nociceptor activation leads to sensitisation of neurones in the trigeminocervical complex, unless the process is blocked or sufficiently limited early‐on with epidural blood patch [4–6, 16, 18, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Although post-dural puncture headache can result in significant shortterm distress and morbidity, the general consensus is that it is a self-limiting condition [8][9][10] and the International Headache Society's definition of post-dural puncture headache reflects this consensus [11]. However, there is emerging evidence from retrospective studies that accidental dural puncture may be associated with persistent headache [12][13][14][15][16][17][18]. In addition, there is low-quality evidence that accidental dural puncture and subsequent epidural blood patch may actually increase the risk of new onset low back pain [17,19,20].…”
Section: Introductionmentioning
confidence: 99%